VITAMIN C DAN KADAR SERAT KASAR PADA STIK BOLU PISANG KEPOK DAN PISANG PISANG - Hamdi Hamdi; Lilik Lilik; Sri Mulyati; Erik Darmansyah (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Banana is a fruit that is often consumed by people compared to other fruits. Regular consumption by the community is due to bananas being a fruit that is always available throughout the year. Bananas spoil quickly when they are ripe, so they need to be processed if they want to be used and have added value. The purpose of this study was to determine the effect of using kepok bananas and pisang pisang on the content of Vitamin C and crude fiber in banana sponge sticks. This research is experimental. Determination of the research unit by purposive sampling. The type of data used in this research is quantitative data. Quantitative data were obtained from the results of the Vitamin C test and the crude fiber content test. Vitamin C analysis was carried out using the iodimetric titration method and fiber content analysis was carried out using the gravimetric method. Conclusion: Vitamin C in banana kepok sponge stick is 5.6099 mg/100 gram, higher than pisang pisang sponge stick, which is 5.5917 mg/100 gram. Crude fiber in banana kepok sponge sticks is 3.6914%, lower than pisang pisang sponge sticks which is 5.9674%.